Edukasi Mengoptimalkan Sumber Daya Untuk Pembuatan Noken Menggunakan Program Linier - Matheus Supriyanto Rumetna; Tirsa Nina Lina; Joseph E. Lopulalan; Jalminj Tindage (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Mr. Meki Murpa is a craftsman as well as a Noken seller with his address at Jalan F. Kalasuat, Sorong City, West Papua. Noken made from Balam bark. This business experienced ups and downs in its journey, this was due to the lack of manpower, Balam wood raw materials and also the Covid-19 pandemic storm. One of the factors that makes it increasingly difficult to find skilled workers in the manufacture of Noken and Balam wood raw materials because Sorong City is starting to experience a shift towards modernization, so there is a lot of development that makes it difficult to get Balam wood. For this reason, the Community Service (PkM) team at Victory Sorong University offers an educational program, namely providing training on optimizing resources for making noken using the Linear Program (PL) and POM-QM software for windows version 5.3. This PkM activity has been successfully implemented, this can be clearly seen by the high enthusiasm of the participants, the increased level of understanding of partners, and a positive impact on all stakeholders involved. The success of this PkM activity is a motivation for the team to continue to do the same thing and even improve the performance of the PkM team.